(untitled) (ADVANCED TECHNOLOGIES AND COMPUTER SCIENCE, 2021)
This article considers the problem of face detection in the case of 3D and discusses the current state of the problem , describes the principles of the existing systems of three-dimensional detection. Methods for solving a key problem in the field of three-dimensional face detection - obtaining three-dimensional information about a face are presented. Common methods of 3D face detection are considered.